Water Quality Dynamics in Kemajuan Lake: Statistical Evaluation Using CTSI and WQI - Muhammad Hafiq Afifi Azman; Azme Khamis; Rafidah Hamdan; Nur Ain Ebas; Zuhaib Siddiqui (International Journal of Sustainable Construction Engineering and Technology, 2026)
Kemajuan Lake, an artificial lake within Universiti Tun Hussein Onn Malaysia (UTHM), faces increasing anthropogenic stress from campus activities and surrounding infrastructure. This study statistically evaluates the lake’s water quality using the Carlson Trophic State Index (CTSI) and the Malaysian Water Quality Index (WQI), supported by correlation analysis, hypothesis testing, ANOVA, F-tests, and paired sample t-tests. Weekly water samples were collected over 40 weeks, analysing physicochemical parameters including turbidity, total suspended solids (TSS), nitrate, ammoniacal nitrogen (AN), temperature, dissolved oxygen (DO), and pH. Based on descriptive analysis, Kemajuan Lake was classified as eutrophic (mean CTSI = 70.23) and slightly polluted (mean WQI = 72.57, Class III under NWQS). The average parameter values were turbidity = 20.70 NTU, TSS = 15.45 mg/L, nitrate = 0.36 mg/L, AN = 0.55 mg/L, temperature = 27.94°C, DO = 4.12 mg/L, and pH = 6.80. Pearson correlation showed a strong positive relationship between CTSI and turbidity (r = 0.648) and moderate negative correlations between WQI and both TSS (r = -0.552) and AN (r = -0.413). Hypothesis testing and ANOVA confirmed significant differences between CTSI and WQI, indicating they reflect distinct water quality attributes. This study concludes that both CTSI and WQI offer complementary insights into eutrophication and general pollution levels and should be applied in tandem for accurate water quality monitoring. The findings support the practical implementation of a dual index monitoring strategy for urban lake management, promoting more targeted remediation efforts, early detection of eutrophication, and sustainable aquatic ecosystem conservation.